Vía pública, vida pública. De los caminos de vida y la calle en la organización urbana - Jesús Galindo Cáceres (Estudios sobre las Culturas Contemporáneas)
To understand urban life, is required to have the descriptive knowlwdge of that urban life. The principle to.get the required knowlwdge is the situacional charts; there all happenings of a vital and colective course get located. This text reflects upon urban life; it touches the city, than complex net of relations seen as an encounter disencounter scenery between thousands of social actors. Public life (life in the street) and private life (domestic life) are sential elements to know the situational environment that envelope cities.